The millipede genus Skleroprotopus Attems, 1901 (Diplopoda, Julida, Mongoliulidae) in China, with description of a new species - Mikhaljova, Elena V.; Kazarin, Vitaly M.; Marusik, Yury M. (Zootaxa, 2024)
The genus Skleroprotopus Attems, 1901 is represented in China by five species, all keyed and mapped, including Skleroprotopus securifer Mikhaljova sp. nov. Taxonomic and distributional remarks are provided for all of the species.